Analisis Biaya Operasional Penambangan Metode Full Costing Pada Tambang Bawah Tanah CV. Tahiti Coal Sangkar Puyuh, Kecamatan Talawi, Kota Sawahlunto - Atha Angely Diansa; Rizto Salia Zakri (Departemen Teknik Pertambangan FT UNP, 2022)
Abstract. Calculation of the cost of production is very important and can be used the basis for preparing Calculation of the cost of production is very important and can be used as the basis for preparing reports. The purpose of this study was to determine the operational costs of mining and to analyze the comparison of the full costing method and the variable costing at CV. Tahiti Coal. Research results and calculations, the total cost of mining operations in CV. Tahiti Coal in January-December 2020, which is Rp.9.897.410.093. The cost of production using the full costing method in the current condition is Rp.357.449/ton and when the condition is reached, the production is Rp.257.355/ton. The variable costing method in the current condition is Rp.346.356/ton and when the condition is reached, the production is Rp.254.795/ton. The total profit earned by CV. Tahiti Coal in January-December 2020 is Rp.13.638.239.907 (full costing method) and Rp.13.945.403.079 (variable costing method).